SOIL PHYSICAL ATTRIBUTES AND YIELD OF WINTER COMMON BEAN CROP UNDER A NO-TILL SYSTEM IN THE BRAZILIAN CERRADO - Cavallini Da Silva, Maria Cecilia [UNESP]; Andreotti, Marcelo [UNESP]; Costa, Nidia Raquel [UNESP]; Da Rocha Lima, Cesar Gustavo [UNESP]; Pariz, Cristiano Magalhaes [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2017)
Knowledge of the interactions between soil physical properties and yield performance in agricultural crops is very important for the adoption of appropriate management practices. This study aimed to evaluate the linear and spatial correlations between some soil physical attributes, straw production in the palisade grass (Urochloa brizantha), and grain yield of winter common bean in succession to the grass under an irrigated no-till system in an Oxisol Haplorthox in the Cerrado lowlands region of Brazil. The plant attributes determined were dry matter yield of U. brizantha (DMY), and grain yield (GY) and final plant population (PP) of winter common bean. The soil physical attributes, evaluated at 0.0-0.10 m and 0.10-0.20 m, were soil bulk density (BD), macroporosity (MA), microporosity (MI), total porosity (TP), penetration resistance (PR), gravimetric water content (GW), and volumetric water content (VW). A geostatistical grid with 124 sampling points was installed to collect the soil and plant data in an area of 4000 m(2). The remaining straw amount of palisade grass exhibited an inverse linear correlation with bean yield and bean plant population when the bean was cultivated in succession. However, no spatial correlations were observed among the attributes. The common bean yield had a direct linear correlation with gravimetric water content in the 0.10-0.20 m soil layer. From a spatial point of view, winter bean yield showed a strong dependence on the distribution of the volumetric water content in the 0-0.10 m soil layer.
Keywords: Geostatistics; Soil physics; Phaseolus vulgaris; Urochloa brizantha; Brazilian Cerrado lowlands